Restoration of Sekar Wilis Local Tourism and Planting Plant Seeds - Zain, Lubby Anwar; Kusnawan, Wawan; Ramadhan, Dimas Dwi (CV. BImbingan Belajar Assyfa, 2023)
This service activity is in partnership with the community and youth organizations in Kesugihan Village. The method used is location survey and situation analysis. The results of the KKN activities are assessment of geographical conditions, repainting and repair of children's play rides, addition of supporting facilities and infrastructure, restoration of toilets and reinstatement of water access, planting plant seeds, adding warning boards, and response from the community. The aim of restoring and planting plant seeds at the local Sekar Wilis tourist location is to ensure that the tourist destination remains attractive and sustainable for visitors as well as provide positive benefits to the environment for local communities and help to rebuild balance and biodiversity. Maintenance of sustainability after restoration and planting of plant seeds is expected to come from the continued participation of the community and local youth organizations in maintaining the local Sekar Wilis tourist attraction. By developing sustainable tourism and focusing on positive values, various positive impacts will be realized so that it can become a source of happiness and prosperity for all parties involved.